KONSOLIDASI TANAH PERKOTAAN SEBAGAI INSTRUMEN PENGADAAN TANAH BAGI KEPENTINGAN UMUM - Isabela Candrakirana; Oloan Sitorus; Widhiana Hestining Puri (BHUMI: Jurnal Agraria dan Pertanahan, 2014)
Land Consolidation (LC) is land policy concerning settlement return the domination and land use as efforts of landacquisition for development interest, to enhance the environment quality and preservation of natural resources by activelyinvolving the community participation. In this case government needn’t to provide compensation with a very large fund due theprinciples used in LC is building without displacing. The LC participants provide Land Contribution for the Development (STUP)that will be used for public and social facility and for the KT implementation fund. KT that mostly conducted in Indonesia is UrbanLand Consolidation (ULC) namely LC which carried out in urban or outskirt. Several countries have implemented this in handlingland acquisition and arrangement issues, such as Japan, Germany and Thailand. This study using case study’s approach which aimto get the comprehensive knowledge about KTP. The ULC is a program that upholds the justice and participatory principle. Thecommunity will receive a decent environment completed with public and social facility, in addition the community is also asked todirectly involve in the activity process start from its planning up to development. Beside that others various public facility whichusually obtained by land acquisition can be fulfilled by the community participation in ULC.Key Words: Urban Land Consolidation, Land Acquisition, Public Interest